Case Report: Extramedullary Acute Promyelocytic Leukemia: An Unusual Case and Mini-Review of the Literature - Harrer, Dennis Christoph; Lüke, Florian; Einspieler, Ingo; Menhart, Karin; Hellwig, Dirk; Utpatel, Kirsten; Herr, Wolfgang; Reichle, Albrecht; Heudobler, Daniel (Frontiers in Oncology, 2022)
Background Acute promyelocytic leukemia (APL) constitutes a serious hematological emergency necessitating rapid diagnosis and therapy to prevent lethal bleedings resulting from APL-induced thrombocytopenia and coagulopathy. Atypical manifestations of APL, such as extramedullary disease at first presentation, pose diagnostic challenges and delay the onset of appropriate therapy. Nevertheless, extramedullary manifestations of APL are mostly accompanied by blood count alterations pointing to an underlying hematological disease. In this report, we present the first case of APL bearing close resemblance to a metastasized laryngeal carcinoma with normal blood counts and absent coagulopathy. Case presentation A 67-year-old man with a previous history of smoking was admitted to our hospital with progressive hoarseness of voice, odynophagia, dysphagia and exertional dyspnea. Laryngoscopy revealed a fixed right hemi larynx with an immobile right vocal fold. Imaging of the neck via magnetic-resonance imaging (MRI) and positron emission tomography–computed tomography (PET/CT) with F-18-fluordeoxyglucose (FDG) showed a large hypermetabolic tumor in the right piriform sinus and tracer uptake in adjacent lymph nodes, highly suspicious of metastasized laryngeal carcinoma. Surprisingly the histological examination revealed an extramedullary manifestation of acute promyelocytic leukemia. Remarkably, blood counts and coagulation parameters were normal. Moreover, no clinical signs of hemorrhage were found. PML-RARA fusion was detected in both laryngeal mass and bone marrow. After diagnosis of APL, ATRA-based chemotherapy was initiated resulting in complete remission of all APL manifestations. Conclusions This is the first case report of APL initially presenting as laryngeal chloroma. Additionally, we performed a comprehensive literature review of previously published extramedullary APL manifestations. In aggregate, a normal blood count at first presentation constitutes an extremely rare finding in patients initially presenting with extramedullary APL manifestations.